Effects of Different Freezing Methods on the Quality Characteristics of Boletus edulis Bull.: Fr. - HUANG Xinyue, WANG Haidan, LI Ronghui, YU Lijuan, ZHANG Guicui, HE Daiqin, MA Feifei (Shipin Kexue)
In this study, the freezing and texture characteristics of Boletus edulis Bull.: Fr. by refrigerator slow freezing (RSF), immersion chilling and freezing (ICF) and liquid nitrogen spray quick-freezing (LNF) were evaluated. The results showed that the quick-frozen samples exhibited shorter time needed to pass through the zone of maximum ice crystal formation and denser ice crystal structure than the slowly frozen samples. The samples treated with LNF at −80 ℃ had the best water-holding capacity. The appearance of the quick-frozen samples was better than that of the slowly frozen samples. In particular, the appearance of the −80 ℃ LNF group was the best. After freezing treatment, both soluble protein and sugar contents tended to increase, while the polyphenol content was reduced. The contents of both soluble protein and sugar were significantly lower in each quick-frozen group than in the RSF group (P < 0.05), while the opposite was observed for the content of polyphenols (P < 0.05). After freezing treatment, the activity of polyphenol oxidase (PPO) significantly rose (P < 0.05), and the −80 ℃ LNF treatment group showed the strongest inhibitory effect against PPO. The activity of superoxide dismutase (SOD) significantly decreased (P < 0.05). The SOD activity (75.82 U/g) of the −100 ℃ LNF group was the closest to that of fresh samples. The samples treated with LNF at −80 ℃ exhibited the tightest binding with water. The microstructure of the slowly frozen samples was ruptured and shrunk with pores. In contrast, the microstructure of the quick-frozen samples was closer to that of fresh samples, and the sensory score was higher than that of the RSF group. In conclusion, LNF treatment can better maintain the quality of frozen B. edulis Bull.: Fr., and LNF at −80 ℃ is the most suitable freezing technology for B. edulis Bull.: Fr., which is expected to become a new choice for the preservation of this mushroom in the future.